Aleppo and its hinterland in the Ottoman period = Alep et sa province à l'époque ottomane - Winter, Stefan, 1970-; Ade, Mafalda (Social, Economic and Political Studies of the Middle East and Asia, 2020)
Aleppo and its Hinterland in the Ottoman Period comprises eleven essays in English and French by leading scholars of Ottoman Syria which draw on new research in Turkish, Levantine and other archival sources. Focusing on both the city and its place in the wider region, the collection examines trade guilds and Christian settlement in Aleppo, Turkmen and Bedouin tribes in Aleppo's interior, international trade and the establishment of an Ottoman commercial tribunal in the Tanzimat period, Aleppo and the rise of the millet system, the Belgian consular presence, Sufi networks in the province of Aleppo, the countryside of Antioch under the Egyptian occupation, and the urban revolt of 1850. With contributions from Enver Çakar, Elyse Semerdjian, Charles Wilkins, Stefan Winter, Mary Momdjian, Bruce Masters, Sylvain Cornac, Mafalda Ade, Feras Krimsti, Nicolas Jodoin, Stefan Knost.